2009
DOI: 10.1371/journal.ppat.1000463
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a SAP18-HDAC1 Complex into HIV-1 Virions and Its Requirement for Viral Replication

Abstract: HIV-1 integrase (IN) is a virally encoded protein required for integration of viral cDNA into host chromosomes. INI1/hSNF5 is a component of the SWI/SNF complex that interacts with HIV-1 IN, is selectively incorporated into HIV-1 (but not other retroviral) virions, and modulates multiple steps, including particle production and infectivity. To gain further insight into the role of INI1 in HIV-1 replication, we screened for INI1-interacting proteins using the yeast two-hybrid system. We found that SAP18 (Sin3a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 48 publications
4
65
2
Order By: Relevance
“…The study also showed that the virion incorporation of HDAC1 plays a role in efficient early post-entry events (38). Since Vpr has already been shown to incorporate one of its target proteins, UNG2, into viral particles (39), it is worth examining whether Vpr plays a role in incorporation of HDACs into the virions or if there is a link between degradation and virion incorporation of HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that the virion incorporation of HDAC1 plays a role in efficient early post-entry events (38). Since Vpr has already been shown to incorporate one of its target proteins, UNG2, into viral particles (39), it is worth examining whether Vpr plays a role in incorporation of HDACs into the virions or if there is a link between degradation and virion incorporation of HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 particles containing the catalytically inactive HDAC1 H141A mutant show reduced deacetylase activity and reduced infectivity. The block due to the presence of the HDAC1 H141A mutant appears to be at or prior to reverse transcription in the target cells [29]. These observations are corroborated by the findings that producer cells lacking INI1 show greatly reduced HIV-1 particle production and that the few particles produced are defective for reverse transcription [26].…”
Section: Introductionmentioning
confidence: 88%
“…INI1 binds to SAP18 (Sin3a associated protein of 18 KD), a component of the Sin3a-HDAC1 complex. In addition to INI1, components of the Sin3a/HDAC1 repressor complex, including SAP18 and HDAC1, are incorporated into HIV-1 virions [29]. HIV-1 particles containing the catalytically inactive HDAC1 H141A mutant show reduced deacetylase activity and reduced infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, INI1/hSNF5 has been shown to be specifically encapsidated into HIV-1 virions, probably through the IN region of Gag-Pol (Yung et al, 2001(Yung et al, , 2004. In addition, a recent study demonstrates that the IN-INI1/hSNF1 interaction selectively recruits SAP18 and HDAC1, components of the Sin3a-HDAC complex, into the HIV-1 virion, increasing the infectivity of the virions (Sorin et al, 2009). Although Huwe1 is an E3 ubiquitin ligase, our study suggests that enzymatic activity of Huwe1 is not involved in the ubiquitination and subsequent proteasomal-degradation of IN and Gag-Pol .…”
Section: Cellular Interactors Affecting On Postintegration Stepsmentioning
confidence: 82%